2013
DOI: 10.1017/s0007114513001736
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal undernutrition programmes thyroid function in the adult rat offspring

Abstract: Increasing evidence suggests that alterations in early nutrition programme physiological changes in adulthood. In the present study, we determined the effects of undernutrition during gestation and lactation on the programming of thyroid function in adult rat offspring. Perinatal undernutrition was achieved by a 40 % food restriction in female Wistar rats from the mating day to weaning. On postpartum day 21, the offspring of the control and food-restricted dams were weaned and given free access to a commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 62 publications
1
21
0
2
Order By: Relevance
“…Many of the molecules critical for HPT axis activity are indeed regulated by TH, but they could also be modulated by other hormones, such as CORT or leptin (22, 47, 48, 64 -66). Nutritional interventions as overfeeding or food restriction during the lactation period, or mother´s malnutrition can affect the expression of several elements involved in the activity of the HPT axis (67)(68)(69). Indirect effects on the development of TRHergic neurons may also occur by defects in their innervations since projections from the arcuate nucleus do not reach the PVN until the second postnatal week, and those arising from the brain stem until the end of the third week (65,70).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the molecules critical for HPT axis activity are indeed regulated by TH, but they could also be modulated by other hormones, such as CORT or leptin (22, 47, 48, 64 -66). Nutritional interventions as overfeeding or food restriction during the lactation period, or mother´s malnutrition can affect the expression of several elements involved in the activity of the HPT axis (67)(68)(69). Indirect effects on the development of TRHergic neurons may also occur by defects in their innervations since projections from the arcuate nucleus do not reach the PVN until the second postnatal week, and those arising from the brain stem until the end of the third week (65,70).…”
Section: Discussionmentioning
confidence: 99%
“…These effects may be sex‐specific, as maternal malnutrition during early gestation increased body mass index (BMI) and waist circumference in 50‐year‐old women but not in men . These findings have been replicated in rodent models, showing that maternal undernutrition programmes severe glucose intolerance and β‐cell dysfunction, dysfunctional skeletal muscle energetics, abnormal mitochondrial function in the heart and changes in the hypothalamus‐pituitary‐thyroid (HPT) axis in offspring …”
Section: Roles Of Maternal Nutrition During Pregnancymentioning
confidence: 98%
“…12 These findings have been replicated in rodent models, showing that maternal undernutrition programmes severe glucose intolerance and β-cell dysfunction, 13 dysfunctional skeletal muscle energetics, 14 abnormal mitochondrial function in the heart 15 and changes in the hypothalamus-pituitary-thyroid (HPT) axis in offspring. 16 Human studies have also demonstrated adverse impacts of maternal overnutrition and obesity in fetal programming. A case-control study performed at Trondheim University Hospital, Norway, suggested that maternal obesity leads to myocardial dysfunction in offspring.…”
Section: Role S Of Maternal N Utriti On During Preg Nan C Ymentioning
confidence: 99%
“…Several experiments in animal models have shown that nutrition (3), hormone-regulated metabolism (4,5), and other toxic influences such as thyroid disruptors affect metabolic and thyroid programming (6). In these conditions, adaptive metabolic strategies in the offspring change the metabolic set points in order to permit survival under critical conditions (7); for example, malnutrition in lactating rats was associated with changes in body weight (3,8) and thyroid dysfunction in their adult offspring (9).…”
Section: Introductionmentioning
confidence: 99%